SYMBOLS, EVIDENCE, AND POLICY: INTEGRATING LEGAL SEMIOTICS FOR SUSTAINABLE CRIME PREVENTION - Debby Ekowati; Retno Saraswati; Nabitatus Sa'adah (Masalah-Masalah Hukum, 2025)
This study explores crime prevention using legal semiotics, applying a doctrinal approach grounded in an extensive literature review and critical text analysis. The discussion is initiated by delineating the core principles of legal semiotics and examining legal norms and practices as sign systems that communicate cultural meanings and influence behaviour. The study examines forensic semiotics, emphasising the role of sign analysis in enhancing investigative procedures and expert linguistic testimony within criminal and civil frameworks, including authorship attribution, identification of falsified texts, and the interpretation of linguistic evidence. Additionally, courtroom discourse and decision-making are also examined, illustrating various semiotic resources (such as text design, layout, and language) influencing the authority and legitimacy of judicial outcomes. Police interactions, interpreting interview dynamics and power negotiations through semiotic frameworks are examined to enhance understanding of witness communication and investigative effectiveness. Furthermore, it examines the framing of crime narratives in the media, highlighting the impact of mediated signs on public perception and the possibility of judicial biases. The research advocates for comprehensive crime prevention policies combining penal and non-penal strategies, emphasizing the importance of symbols and meanings that underpin criminal behaviour to promote collaborative, culturally informed, and sustainable responses.